2022
DOI: 10.1177/00202940221103622
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid CNN-BiLSTM approach for remaining useful life prediction of EVs lithium-Ion battery

Abstract: For accelerating the technology development and facilitating the reliable operation of lithium-ion batteries, accurate prediction for battery remaining useful life (RUL) are both critical. In this paper, a 1D CNN-BiLSTM method is proposed to extract the RUL prediction of lithium-ion battery of Electric Vehicles (EVs). By using one dimensional convolutional neural network (1D CNN) and bidirectional long short-term memory (BiLSTM) neural network simultaneously, selecting the ELU activation function to apply to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The suggested approach not only captures the capacity renewal phenomenon well, but also has good forecast accuracy and is less affected by various prediction starting points. Furthermore, to fully exploit the time-series properties of the lithium-ion battery data, Gao et al [40] combined a convolutional neural network (CNN) and a bidirectional long and short-term memory (BiLSTM) neural network to extract deep features of battery capacity data, and they chose the memory function of the BiLSTM neural network to retain key information in the data and predict the trend of variations in the RUL of batteries. It is crucial to remember that the aging battery data drastically restricts the precision and stability of the data-driven algorithm.…”
Section: Lifetime Prediction For Lithium-ion Batteriesmentioning
confidence: 99%
“…The suggested approach not only captures the capacity renewal phenomenon well, but also has good forecast accuracy and is less affected by various prediction starting points. Furthermore, to fully exploit the time-series properties of the lithium-ion battery data, Gao et al [40] combined a convolutional neural network (CNN) and a bidirectional long and short-term memory (BiLSTM) neural network to extract deep features of battery capacity data, and they chose the memory function of the BiLSTM neural network to retain key information in the data and predict the trend of variations in the RUL of batteries. It is crucial to remember that the aging battery data drastically restricts the precision and stability of the data-driven algorithm.…”
Section: Lifetime Prediction For Lithium-ion Batteriesmentioning
confidence: 99%
“…Accurately predicting the RUL is crucial for ensuring the reliable operation of batteries throughout their entire energy storage lifespan. The capacity is broadly regarded as a sign of health, which is used to evaluate the remaining cycle life of a battery [6,7]. Lithium-ion batteries are dynamic and ever-changing electrochemical systems with nonlinear characteristics and complex internal mechanisms, which exposes great challenges for predicting maximum remaining capacity and minimizing the declining trend.…”
Section: Introductionmentioning
confidence: 99%
“…However, There are few studies on preventive maintenance of brake disc damage monitoring by CNN-LSTM hybrid algorithm. Gao Dexin et al [7] used CNN-LSTM combination to monitor the performance of automotive lithium-ion batteries, and the research showed that the efficiency of CNN-LSTM algorithm were superior to other algorithms, indicating that the method was also suitable for preventive maintenance of brake pads.…”
Section: Introductionmentioning
confidence: 99%